Pengaruh Konsentrasi Awal terhadap Penyerapan Ion Logam Cr+6 menggunakan Biomassa Alga Hijau Mougeotia Sp yang Diimobilisasi dengan Natrium Silika - Mulya Dwi Arif; Mawardi Anwar (Jurnal Periodic Jurusan Kimia UNP, 2020)
Mougeotia Sp green algae biomass is a biosorbent used in the absorption of heavy metals in industrial waste, because of the presence of functional groups that bind to heavy metal ions. However, it has one disadvantage: it is easily damaged by other microorganisms. To improve the physical and chemical properties of algae it is necessary to immobilize the sodium silica. This study aims to determine the maximum absorption and absorption capacity of Cr+6 metal ions by immobilized green algae Mougeotia Sp using sodium silica with a contact technique using a column and measured by Atomic Absorption Spectrophotometer (AAS). The data obtained showed that the interaction between metal ions and the algal biomass of Mougeotia Sp immobilized on sodium silica obtained the optimum concentration at 250 mg /L. The maximum absorption capacity is 7.5815 mg / g with absorption efficiency of 52.0653%. Furthermore, characterization using FTIR shows that functional groups with active mean are silanol and siloxane which are the binding sites for functional groups such as cacbixyl, carbonyl and amines. The biosorption of Cr + 6 metal ions using Mougeotia Sp green algae biomass immobilized with sodium silica fulfills the Langmuir isotherm equation with a regression coefficient (R2) of 0.9294.